Does Charity Begin at Home or Overseas?. (October 2017) - Knowles, Stephen; Sullivan, Trudy
We conducted a field experiment to find out whether a sample of the New Zealand general public preferred to give money to World Vision, an international development charity, or the Salvation Army, a local charity helping families in need. The majority of participants revealed a preference for giving to the local charity, rather than the international development charity. Participants were given the option of commenting on why they chose the charity they did, and we analyze these responses. We also analyze whether participants' individual characteristics are correlated with the choice of charity.